Strategi Komunikasi Dakwah Yayasan Al-Ishlahiyah Dalam Menanggulangi Masalah Putus Sekolah Di Desa Gaung Asam Kabupaten Muara Enim - Hindayani, Hindayani; Noviza, Neni; Marianti, Lena (Journal of Innovative and Creativity, 2026)
This study aims to examine the preaching communication strategy of Yayasan Al-Ishlahiyah and to identify the supporting and inhibiting factors encountered by Yayasan Al-Ishlahiyah in implementing the preaching communication strategy to address the problem of school dropouts. The study employed a descriptive qualitative method using interviews, observations, and documentation techniques involving parties from Yayasan Al-Ishlahiyah. The results of this study indicate that the preaching communication strategy implemented by Yayasan Al-Ishlahiyah is an approach designed in a structured, directed, and comprehensive manner to respond to the issue of school dropouts. The supporting and inhibiting factors of the preaching communication strategy applied by Yayasan Al-Ishlahiyah in Desa Gaung Asam are characterized by a systematic, persuasive, and contextual approach in addressing the problem of children dropping out of school.